Diagnóstico de salud bucodental y factores de riesgo en el centro educativo secundario Abdón Calderón Muñoz de la parroquia Santiago del cantón Loja año 2013. - Tapia Romero, Lesli Lisseth (2013)
The oral diseases are a major problem in our country and in the South is an important index so Loja Canton is not exempt from this reality in both its rural and urban parishes. The research work aims to make the diagnosis center oral health of secondary school students "Abdon Calderon Muñoz" of Loja Canton Santiago parish 2013. This project is descriptive, prospective, cross, is working with 119 high school students. In the rural parish of the canton Santiago Loja, school teens from 99.1% had dental caries, 74.8% of gingival inflammation and gingival bleeding 30.3%, and 31.09% altered occlusion. In habits found was a 2.5% of mouth breathers, and within the pathologies that are most often impacted anterior crossbite with 9.2%, 6.7% of the population with deep bite. It also showed the presence of mild dental fluorosis with 15.1%. The results were collected through a survey and History Dental Clinic, showing that the whole group showed abnormal examined his mouth. Keywords: Oral Health, Risk Factors, Dental Caries, Gingival Inflammation.